Caracterización socioeconómica y vocacional de estudiantes de últimos grados de bachillerato en colegios públicos y privados: el caso del Área Metropolitana de Bucaramanga (2016)
This document aimed to characterize socioeconomically and vocationally young people in a pilot public and private schools BFA degree eleven sample in order to guide public policies aimed at reducing youth unemployment and fomenter best practices of vocational guidance. As work methodology descriptive approach was raised by the application of a survey (web application) provided by the United Nations Development Programme. This work was done within the framework of the research proposed by the Regional Labour Market Observatory, ORMET, Santander sponsored by the Ministry of Labor and the United Nations Development Programme.